2017
DOI: 10.3892/mco.2017.1342
|View full text |Cite
|
Sign up to set email alerts
|

Value of neutrophil-to-lymphocyte ratio for predicting lung cancer prognosis: A meta-analysis of 7,219 patients

Abstract: Abstract. Current evidence suggests that the neutrophil-to-lymphocyte ratio (NLR) may be a biomarker for poor prognosis in lung cancer, although this association remains controversial. Therefore, a meta-analysis was performed to evaluate the association between NLR and lung cancer outcome. A systematic literature search was performed through the PubMed, Embase and Cochrane Library databases (until July 30, 2016), to identify studies evaluating the association between NLR and overall survival (OS) and/or progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 57 publications
4
84
1
2
Order By: Relevance
“…Moreover, there is no exact cut-off point for NLR that can be applied in clinical practice. Almost every study reports its own cut-off for NLR, ranging from 2.11 to 5, although the best cut-off value derived in meta-analysis seems to be ≥ 4 [19,20,21]. We found that an NLR ≥ 4.39 was associated with worse survival in our patient population.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, there is no exact cut-off point for NLR that can be applied in clinical practice. Almost every study reports its own cut-off for NLR, ranging from 2.11 to 5, although the best cut-off value derived in meta-analysis seems to be ≥ 4 [19,20,21]. We found that an NLR ≥ 4.39 was associated with worse survival in our patient population.…”
Section: Discussionmentioning
confidence: 56%
“…Several laboratory markers of SI have been confirmed as prognostic factors in many types of cancer, including plasma concentration of albumin, C-reactive protein, hemoglobin, platelets, and absolute values of white cells and its components (neutrophils, lymphocytes, monocytes) [16]. The neutrophil to lymphocyte ratio (NLR) is one of the most easy and inexpensive methods to estimate SI, and its value as a prognostic factor has been recognized in a wide variety of tumors, including NSCLC in both early and advanced stages [17,18,19,20,21]. However, information about the prognostic significance of NLR in EGFR-mutant advanced NSCLC is scarce, and almost all of the studies published to date have been conducted in Asian populations [20,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to lung cancer, however, most previous studies on NLR or PLR in lung cancer have focused on the prognostic role of NLR or PLR, demonstrating that elevated PLR and elevated NLR are associated with poor prognosis in patients with lung cancer . Until now, only one study has evaluated the association of NLR and PLR with development of lung cancer in individuals without lung cancer at baseline .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several meta-analyses 13,14 with regard to the prognostic role of NLR in cancer targeted therapy or chemotherapy were published. These studies have shown the value of NLR as a biomarker in predicting outcomes of patients with advanced lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-based parameters, such as NLR, have been reported to predict outcomes in cancer patients. A number of meta-analyses 13–15 have suggested that NLR is a good predictive biomarker in predicting efficacy of chemotherapy and molecular targeted therapy in various cancer types. Since 2017, retrospective studies 5,1619 evaluating the role of NLR in predicting outcomes of NSCLC patients receiving immune checkpoint inhibitors have been released.…”
Section: Introductionmentioning
confidence: 99%